Effects of pre-operative instruction about early ambulation on patients' post-operative performance of selected pre-ambulation tasks - Cana, Racquel P.
The present study investigated the problem: "Will structured individualized instruction on early ambulation given by the nurse pre-operatively to adult surgical patients' level of performance of post-operative pre-ambulation tasks?" The pre-ambulation tasks were deep breathing exercise, log exercises, and turning to either sides. The purpose of the study was to find out whether the pre-operative instruction given to the patients would result in early, frequent, spontaneous and independent performances of the pre-ambulation tasks during the immediate post-operative period. The null hypothesis tested was: that adult surgical patients who received pre-operative structured instruction from the nurse regarding three tasks of an immediate post-operative early ambulation program will have the same level of performance of the tasks as those patients who did not received similar ...
Thesis (Master of Arts in Nursing) -- University of the Philippines
Keywords: Operations, surgical